2009
DOI: 10.1037/a0017000
|View full text |Cite
|
Sign up to set email alerts
|

When the shoe is on the other foot: A qualitative study of intern-level trainees’ perceived learning from clients.

Abstract: Twelve trainees (3 men and 9 women) who had recently completed predoctoral internships at a university counseling center were interviewed about what they had learned from clients. Data were analyzed using a consensual qualitative research method. Participants reported learning things about doing therapy, themselves, client dynamics, human nature, the therapy relationship, and the usefulness of supervision. In addition, participants highlighted the importance of consultation and self-reflection to help them rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…They found evidence for the effectiveness of all four components, but by far they found that practice was cited as the most helpful component. Similarly, psychology externs and interns reported learning a lot from their experiences seeing clients (Hill et al 2014;Stahl et al, 2009). Personal therapy.…”
Section: Mechanisms Of Changementioning
confidence: 99%
“…They found evidence for the effectiveness of all four components, but by far they found that practice was cited as the most helpful component. Similarly, psychology externs and interns reported learning a lot from their experiences seeing clients (Hill et al 2014;Stahl et al, 2009). Personal therapy.…”
Section: Mechanisms Of Changementioning
confidence: 99%
“…Participants as therapists, for instance, may have quite divergent thoughts and feelings about their crying in that role than they do when crying as clients in their own therapy, or when their own therapists cry with them in therapy. Furthermore, having found therapists-in-training quite thoughtful, reflective, and willing to discuss such experiences, we deliberately sought trainees as our participants, as has been the case with other recent research (Hess et al, 2008; Hill et al, 2015; Hill, Sullivan, Knox, & Schlosser, 2007; Stahl et al, 2009). In addition, by having doctoral students as participants, we could begin to examine the role of therapist experience, in that doctoral students may have different experiences crying as therapists than do the more experienced practitioners with whom they work.…”
Section: Current Studymentioning
confidence: 99%
“…We concur with Hill and Lent's (2006b) conclusion that helping skills training is only the first step in a journey of therapist development and that the best way to continue learning helping skills is through continued practice (e.g., in practicum, externships, predoctoral internship, etc.). Specifically, trainees should see lots of clients in individual therapy, given that research on therapist development indicates that psychotherapists attribute the majority of their learning about therapy to clients (e.g., Goldfried, 2001; Orlinsky, Botermans, & Rønnestad, 2001; Rønnestad & Skovholt, 2003; Skovholt & McCarthy, 1988; Stahl et al, 2006). Furthermore, Stahl et al (2006) found that interns learn both about specific response modes and additional skills from their work with clients, suggesting that continued work with clients contributes to trainees' growing knowledge about helping skills.…”
Section: After Helping Skills Trainingmentioning
confidence: 99%